Quality of Life of Individuals Having OCD With and Without Co- morbid Psychiatric Disorders - Tamkeen Saleem, Seema Gul, Muhammad Tahir Khalily (Pakistan Journal of Psychology, 2012)
This study aims to investigate the quality of life of individuals having obsessive compulsive disorder (OCD) as their principal diagnosis with comorbid psychiatric disorders. It was hypothesized that individuals having obsessive compulsive disorder with comorbid psychiatric disorders have poor quality of life as compare to individuals having OCD without co morbid psychiatric disorders. 80 individuals (40 males and 40 females) with a primary diagnoses of obsessive compulsive disorder ranging from ages 25 to 40 years with Mean age=32 years were included in this study. We used Yale Brown Obsessive Compulsive Scale (Y-BOCS; Goodman, Price, Rasmussen, et al, 1989) and World Health Organization Quality of Life Bref (WHOQOL Bref; Orley, Kuyken, Satorious, et al., 1994) instruments for this purpose. Our findings indicated that individuals having obsessive compulsive disorder with co morbid psychiatric disorders have poor quality of life as compared to individuals having OCD without co morbid psychiatric disorders.